RELIGIUSITAS DAN KESEJAHTERAAN PADA MASYARAKAT MISKIN (Di Desa Lubuk Gaung Kecamatan Siak Kecil Kabupaten Bengkalis) - ", Suhendar; ", Basri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Well-being is a condition generally expected by every people in gething safe life and piece. Well-being means that a human condition that releaged from disuption in their life. There are many ways that used by the humans to find the well-being in their life. Beside that, religion clearly help the humans to choose good way to find the well-being in their life and the beyond. This study purposed to find out empirically the correlation between religiosity and well-being in Lubuk Gaung village Siak Kecil district. The hyphotesis in this study is” There is correlation between religiosity and well-being in destitute people. With the population 185 people, the subject of this research is 156 people.Data correlation technique that used in this research is religiosity scale and well-being scale from (Glock and Stark). Data analysis technique that used in this study is (product momen). The result indicated that there is positif correlation that very significant between religiosity and well-being in destitute people. 0,401 in significant phase 0,000 (< 0,001). It means that religiosity has the significant effect to the well-being. With categorizes the grade of religiosity lowest 0 people (0%), low 5 people (3,20%), middle 70 people (44,88%), high 39 people (25%), and highest 42 people (26,92%). And then in well-being, lowest 11 people (7,1%), low 34 people (21,8%), middle 67 peopele (43 %), high 29 people (18,5 %) and highest is people (9,6%).Keyword; Religiosity, Well-being, And Destitute People